Soviet Strategy for Economic Growth Selected Soviet Essays, 1924-1930 - Spulber, Nicolas (Indiana University Press, 1964)
Soviet Strategy for Economic Growth examines the Soviet goals and concepts of economic development; views of the economy as a "going concern;" strategies for carrying out these goals; concepts of growth and efficiency; and planning solutions-as formulated on the eve of the Soviet era of "all-out" industrialization and comprehensive planning and as modified since then.